Decision constructive-technically tasks in conditions of deformation of tasks maintenance - Berezova, L. V. (НУБіП України, 2018)
Tasks, questions and practical tasks is an effective didactic way, which makes active creative activity of the person. The constructive thinking carried out at the decision of creative tasks is considered. Analyses of creative technical thinking development and the peculiarities of the constructive-technical tasks solving are given. The creative thinking is a search and opening something new, for creative work, it is necessary to own ability independently and critically to think. On the basis of the main ways, methods of the solution strategy of the task solution is formed. Transformation of the solution strategy of the constructive-technical tasks with use of complications is considered.
Розв’язування конструктивно-технічних задач в умовах деформації їх змісту
Задачі, запитання та практичні завдання, є ефективним дидактичним засобом, який робить активної творчої діяльності людини. Конструктивне мислення здійснюється при вирішенні творчих завдань. Аналіз творчих розвитку технічного мислення і особливості Конструктивно-технічного рішення завдань. Творче мислення-це пошук і відкриття чогось нового, для творчості, потрібно володіти здатність самостійно і критично мислити. Виходячи з основних напрямів, сформованих методами стратегії вирішення завдань рішення. Трансформація стратегії рішення конструктивнотехнічної задачі з використанням ускладнень є.
Keywords: creative thinking; transformation of strategy; constructive-technical task; solution of tasks; complication; трансформація; творче мислення; стратегії; конструктивно-технічних задач; ускладнення; вирішення завдань